2020
DOI: 10.1021/jacs.0c00459
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Walled Knotted Cage for Guest-Adaptive Molecular Recognition

Abstract: We synthesized a double-walled knotted cage from a flexible tripodal ligand. The characteristic double-walled structure provided a unique adaptive behavior of the cavity upon inclusion of organic molecules, which was evidenced by NMR and X-ray measurements. The semiflexible host framework, restricted by the knotted topology, enabled kinetic molecular recognition revealing the sequential binding of two different guests from their mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 47 publications
(14 reference statements)
1
51
0
Order By: Relevance
“…For the construction of Pd II -based metal-ligand assemblies, polydentate N-donor ligands were found to be well suited. [12][13][14][15][16][17] Elaborate polypyridyl ligands were used to build complex molecular architectures, [18][19][20][21][22][23][24][25] but even simple di-4-pyridyl ligands can give rise to assemblies with up to 48 Pd II ions. [26] A crucial design element for di-4-pyridyl ligands is the bent angle α between the two coordinate vectors of the pyridyl groups (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…For the construction of Pd II -based metal-ligand assemblies, polydentate N-donor ligands were found to be well suited. [12][13][14][15][16][17] Elaborate polypyridyl ligands were used to build complex molecular architectures, [18][19][20][21][22][23][24][25] but even simple di-4-pyridyl ligands can give rise to assemblies with up to 48 Pd II ions. [26] A crucial design element for di-4-pyridyl ligands is the bent angle α between the two coordinate vectors of the pyridyl groups (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…reported the first tetrahedron‐shaped, double‐walled complex that contains two different C 3 ‐symmetric ligands based on the slight mismatch of metal ion and ligand [24] . A thorium‐based MOF featuring a double‐walled tetrahedral cage structure was synthesized by Xing and Bai, [25] while an M 12 L 8 (M=Pd) double‐walled, knotted cage was constructed by Fujita et al [26] . Very recently, a molecular‐strain‐engineered double‐walled tetrahedron was also reported [27] .…”
Section: Resultsmentioning
confidence: 99%
“…There are only very few examples of metal-based, doublewalled tetrahedra in the literature.O ppel et al reported the first tetrahedron-shaped, double-walled complex that contains two different C 3 -symmetric ligands based on the slight mismatch of metal ion and ligand. [24] At horium-based MOF featuring ad ouble-walled tetrahedral cage structure was synthesized by Xing and Bai, [25] while an M 12 L 8 (M = Pd) double-walled, knotted cage was constructed by Fujita et al [26] Very recently,amolecular-strain-engineered doublewalled tetrahedron was also reported. [27] In all of these examples,the ligands (same or different) serve as the double walls of the tetrahedron, while the metal ions are either located within the faces or at the vertices.Inasharp contrast, in the current work, the anion itself serves as one (outer) of the walls,thus representing adifferent assembling mode.…”
Section: Hnmr Dosye Si-msa Nd Theoretical Structural Optimization Res...mentioning
confidence: 99%
“…There are only very few examples of metal-based, doublewalled tetrahedra in the literature.O ppel et al reported the first tetrahedron-shaped, double-walled complex that contains two different C 3 -symmetric ligands based on the slight mismatch of metal ion and ligand. [24] At horium-based MOF featuring ad ouble-walled tetrahedral cage structure was synthesized by Xing and Bai, [25] while an M 12 L 8 (M = Pd) double-walled, knotted cage was constructed by Fujita et al [26] Very recently,amolecular-strain-engineered doublewalled tetrahedron was also reported. [27] In all of these examples,the ligands (same or different) serve as the double walls of the tetrahedron, while the metal ions are either located within the faces or at the vertices.Inasharp contrast, in the current work, the anion itself serves as one (outer) of the walls,thus representing adifferent assembling mode.…”
Section: Methodsmentioning
confidence: 99%